SAVING AND LOAN ACCOUNTING INFORMATION SYSTEM AND FINANCIAL STATEMENT ANALYSIS USING CLIENT SERVER-BASED FINANCIAL RATIOS METHOD (CASE STUDY IN THE KOSCOMINDO EMPLOYEE COOPERATIVE SEMARANG) - Lati Fatur Rizma; Nuris Dwi Setiawan (Journal of Engineering, Electrical and Informatics, 2021)
When presented with an accounting information system based on a reliable system, it will certainly produce objective information as well. One way to achieve a reliable accounting system is by utilizing information technology which is currently being developed. Computerized transaction management is very beneficial for the savings and loan business unit because there are transactions that occur regularly or repeatedly. Likewise, in presenting financial statements where financial statements are records of a company's financial information during an accounting period that can be used to describe the company's performance. while financial analysis is used to assess business continuity, stability, profitability of a business, sub-business or project. Koperasi Koscomindo which is a financial institution in making customer reports, savings, loans and installments, as well as monthly and annual financial reports still rely on Ms. Excel which still needs processing first because it has to combine data from books, both savings, loans and installments so that the leader cannot receive reports quickly and accurately. Likewise, in analyzing financial statements, this process makes it difficult for management to make decisions quickly For this reason, a design of a savings and loan accounting information system that can process data on members, savings, loans, installments and analysis of financial statements is made more effectively and has high accuracy using a computer, with Visual Basic and Microsoft SQL Server programming languages and in financial analysis. which is used with the Financial Ratio method. From the results of the program that has been made to help reduce errors in data entered, financial reports and financial analysis can be produced more quickly and effective and efficient achievements can be made.